PENGARUH METODE CINEMA EDUCATION TERHADAP PRESTASI BELAJAR SEJARAH KEBUDAYAAN ISLAM DI MADRASAH QUR’ANIYYAH AL-HUSNAYAIN SURAKARTA TAHUN AJARAN 2024/2025 - Itsnainiyah Izzah; Iffah Mukhlisah, S.Pd.,M.Pd; Septian Ika Trisnawati, M.Pd., CLSP (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to: 1) find out how high the Cinema Education method is inMadrasah Qur'aniyyah Al-Husnayain Surakarta; 2) find out how high the learningachievement of Islamic cultural history is in Madrasah Qur'aniyyah Al-HusanyainSurakarta; 3) find out how big the influence of the cinema education method is on the learning achievement of Islamic cultural history in Madrasah Qur'aniyyah Al-Husanyain Surakarta. This study uses a correlational research type with a quantitative approach. The place and time of this research are at MadrasahQur'aniyyah Al-Husnayain Surakarta in May-June. The population of this study is 34students of grades VII, VIII, IX Madrasah Qur'aniyyah Al-Husnayain Surakarta in the2024/2025 Academic Year. The sample in this study uses a saturated sample. Andthe data collection method used in the cinema education method is a questionnaireand learning achievement of Islamic cultural history using an essay test. The validitytest uses the product moment formula and the reliability test uses Cronbach's alpha,the prerequisite test uses the normality test with the Shapiro Wilk formula, and thelinearity test takes a linear regression equation model, the hypothesis test usesproduct moment correlation. The results of this study indicate that: 1) the cinemaeducation method at Madrasah Qur'aniyyah AL-Husnayain Surakarta in the2022/2025 Academic Year has the highest value of 71 with a very good categoryand the lowest value of 41 with a fairly good category with an average value of58.4118. 2) the results of the Islamic Cultural History Learning achievement havethe highest value of 100 and the lowest value of 70 with an average of 94.35. 3) TheEffect of the Cinema Education Method on the Learning Achievement of IslamicCultural History at Madrasah Qur'aniyyah Al-Husnayain Surakarta in the 2024/2025Academic Year found the results of r-count 0.961> r-table 0.339 and found asignificance value of 0.000 <0.05 thus the alternative hypothesis is accepted. It canbe concluded that there is an influence of the Cinema Education Method on the learning achievement of Islamic Cultural History at Madrasah Qur'aniyyah Al-Husnayain Surakarta in the 2024/2025 academic year.